Biocompatible Mg–Al2O3–TiO2 hybrid nanocomposites: influence of fillers on mechanical and corrosion properties - Neela Murali, V.K; Starvin, M.S; I, Siva; Sultan, M.T.H (Elsevier, 2024)
A hybrid Mg composite filled with micro Al2O3 and nano TiO2 is manufactured through a blend press sinter powder metallurgy route. To appraise the significance of filler incorporation on the mechanical and corrosion strength, the composite is undergoing a series of characterizations. Initially the filler distribution was analyzed through electron microscopes. Static mechanical tests as per ASTM are conducted to measure the influence of fillers on the tensile and compression properties. The corrosion characteristics were studied by immersing the composites into the laboratory synthesized stimulated body fluid (SBF). Through the Tafel Polarization, the corroded surfaces are examined. The corrosion resistance of the composites exhibited a change that closely resembled that of pure magnesium. Based on the experimental findings, it appears that the composite being examined is well-suited for various biomedical applications, particularly in the field of dental implants.